Medical Metaphors in Byzantine Spiritual Direction. - Zecher, Jonathan L. (Journal of Religion, 2022)
John of Sinai, better known as John Klimakos (sixth or seventh century), wrote two enormously popular works: the Ladder of Divine Ascent , and its short sequel, To the Shepherd. In these he frequently invoked medical, pedagogical, and judicial metaphors to articulate a synoptic view of monastic spiritual direction. While scholars have noted John's medical language, they have not attended to the cultural and epistemic contexts of medical knowledge and practice in late antiquity that recent studies in early Christian medical metaphors have highlighted. This study engages Paul Ricoeur's work on metaphor to analyze the lengthiest and most detailed medical metaphors in the Ladder and Shepherd and to demonstrate that an intimate familiarity with medical theories and clinical practice constrains, organizes, and constructs spiritual direction in his work. The conclusion develops the idea of Byzantine monasteries as textual communities, in which the Ladder plays an important formative role, and shows that medical metaphors were integral to the constitution of Byzantine monastic communities and subjectivities.